Prognostic role risk factors in rehabilitation of patients with cardiovascular diseases. - Manshulovsky V.M; Mohammed Ali; Lukasevych I.I (Kharkov National Pedagogical University, 2011)
Modern views on the reasons of high mortality of the population from cardiovascular diseases are considered. It is shown that the death rate is defined by quantity of risk factors and their various combinations. The analysis of publications of various authors about the most important risk factors - essential hypertension, hypercholesterolemia, hypokinesias and smoking is carried out. The opinion that the most important risk factors is hypokinesia of the person is expressed. It is offered to include the physiotherapy exercises in schemes of physical rehabilitation of patients for struggle (fight) with hypokinesia as means of prevention maintenance of cardiovascular disease.